Functional neurological disorder: Clinical manifestations and comorbidities; an online survey. (April 2023) - Ducroizet, Alexandra; Zimianti, Ioanna; Golder, Dawn; Hearne, Kim; Edwards, Mark; Nielsen, Glenn; Coebergh, Jan
Highlights: Many co-morbidities arise after FND diagnosis. High levels of pain, fatigue and sleep problems before FND diagnosis. Fibromyalgia and CFS/ME were the commonest co-morbidities in this population. High rate of dissatisfaction with care provision. Abstract: Functional Neurological Disorder (FND) is common and is often accompanied by multiple comorbid symptoms and conditions. There have been no large-scale studies exploring the change of its clinical manifestations and comorbidities. We used an online survey to assess FND patient characteristics, changes to fatigue, sleep and pain and comorbid symptoms and diagnoses, as well as treatment strategies. The survey was shared via the charities FND Action and FND Hope. 527 participants were included in the analysis. Most (97.3%) reported experiencing more than one core FND symptom. Many respondents reported associated pain (78.1%), fatigue (78.0%) and sleep disturbances (46.7%) before FND diagnosis which often increased thereafter. Rates of obesity were higher (36.9%) than in the general population. Obesity was associated with increased pain, fatigue and sleep difficulties. There was frequent weight gain after diagnosis. 50.0% of participants reported having other diagnoses prior to FND, while in 43.3% new comorbidities arise after FND diagnosis. Many respondents reported being dissatisfied with their care, expressing a wish for further follow-up from mental health (32.7%) and/or neurological services (44.3%). This large online survey further supports the phenotypic complexity of FND. High rates of pain, fatigue and sleep disturbance exist before diagnosis but monitoring for change is worthwhile. Our study identified major gaps in service provision; we highlight the importance of an open mind regarding change in symptoms; this could aid the early identification and management of co-morbidities, including obesity and migraine, which possibly have a negative impact on FND.